The Challenges of The Digital Era When Making Reservations at Ragunan Wildlife Park DKI Jakarta - Awaloedin, Dipa Teruna; Nugraha, Rizki Nurul; Achyarsyah, Padri (West Science Interdisciplinary Studies, 2024)
This research is entitled The Challenges of the Digital Era When Making Reservations at the Ragunan Wildlife Park DKI Jakarta. This research discusses the challenges of the digital era when making reservations at the Ragunan Wildlife Park DKI Jakarta. Previously, reservations required intensive efforts and relied on traditional sources of information, but with the development of technology, reservations have become more digital. This research has significant positive impacts on various aspects of life and business such as ease of reservation, operational efficiency and improved visitor experience. This research aims to determine the challenges faced in reservations at Ragunan Wildlife Park and find effective solutions to improve service quality and visitor experience. This research was conducted in the Ragunan Wildlife Park area, Pasar Minggu, Jakarta. The research method used was descriptive qualitative with SWOC analysis to identify factors affecting reservation challenges in the digital era. The results of the SWOC analysis show strategies to utilize strengths, overcome weaknesses, take advantage of opportunities, and overcome challenges. Strategy formulation includes updating the online reservation system, collaborating with third parties, improving technological infrastructure, and increasing server capacity.